2007
DOI: 10.1016/j.ajo.2007.06.032
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Strabismus on Quality of Life in Adults

Abstract: Purpose: As a first step in the development of a health related quality of life instrument, we conducted in-depth interviews to identify the specific concerns of adults with strabismus. Design: Prospective cross-sectional studyMethods: Thirty adults with strabismus, 17 with diplopia and 13 without were recruited. Individual interviews, using 11 open-ended questions, were audiotaped, transcribed and transcripts reviewed independently by 3 investigators. Phrases regarding how strabismus affected everyday life we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
92
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 124 publications
(103 citation statements)
references
References 13 publications
4
92
0
Order By: Relevance
“…Second, strabismic adults have been shown to have social and psychological issues directly related to their condition, which impact all aspects of their lives: education, social relationships, employment prospects, and self-esteem. [2][3][4][5][6][7] One study has shown that manifest strabismus has a direct relationship with mental health issues, which occur more commonly when compared with controls. 8 A review of the psychosocial issues associated with squint concluded thus, 'There is overwhelming evidence describing these negative effects on patients.'…”
Section: Introductionmentioning
confidence: 99%
“…Second, strabismic adults have been shown to have social and psychological issues directly related to their condition, which impact all aspects of their lives: education, social relationships, employment prospects, and self-esteem. [2][3][4][5][6][7] One study has shown that manifest strabismus has a direct relationship with mental health issues, which occur more commonly when compared with controls. 8 A review of the psychosocial issues associated with squint concluded thus, 'There is overwhelming evidence describing these negative effects on patients.'…”
Section: Introductionmentioning
confidence: 99%
“…Using extraction techniques, items were created from phrases in patient interviews. 21 A total of 181 items were then completed by a group of strabismus patients and then reduced to 20 items using factor analysis. 19 The two subscales of psychosocial concerns and functional difficulties possess good discriminative ability, internal consistency, 18 and testeretest reliability.…”
mentioning
confidence: 99%
“…Negative psychological effects of strabismus in adults include a negative self-image such as a lack of confidence and a low self-esteem and negatively affect job prospects, relationships, education and sports (Kothari et al, 2009;Burke et al, 1997;Hatt et al, 2007;Nelson et al 2008;Jakson et al, 2006;Durmian et al, 2009;Bez et al 2009). These difficulties have been reported to worsen both with increasing age and the severity of the strabismus (Durmian et al, 2009).…”
Section: Original Articlementioning
confidence: 99%